2013
DOI: 10.1111/appy.12067
|View full text |Cite
|
Sign up to set email alerts
|

Stressors in secondary boarding school students: Association with stress, anxiety and depressive symptoms

Abstract: Introduction: Chronic stress in adolescents may cause physical, mental and emotional health issues which lead to poor outcomes if left untreated. The present study aimed to determine the prevalence of depression, anxiety and stress, and their association with stressors. Methods: A cross-sectional study was conducted among 350 students in a selected boarding school. Two validated Malay version questionnaires were used as instruments, which comprised the 21-item Depression, Anxiety and Stress Scale to assess dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 26 publications
(20 reference statements)
9
30
2
3
Order By: Relevance
“…Study by Wahab S et al, among secondary boarding school students in Malaysia showed the prevalences of depression, anxiety and stress as 39.7%, 67.1% and 44.9% respectively. 6 The results of depression and anxiety are much lower than the results of our study whereas stress is significantly higher in their study.…”
Section: Discussioncontrasting
confidence: 81%
“…Study by Wahab S et al, among secondary boarding school students in Malaysia showed the prevalences of depression, anxiety and stress as 39.7%, 67.1% and 44.9% respectively. 6 The results of depression and anxiety are much lower than the results of our study whereas stress is significantly higher in their study.…”
Section: Discussioncontrasting
confidence: 81%
“…Mathematics, Physics, English Language and History). A similar study, by Wahab et al ( 2013 ), focusing on total 360 secondary boarding school students (16 years old in average) in Malaysia, revealed that the prevalence of stress, anxiety and depression was slightly higher (39.7%, 67.1% and 44.9%, respectively) compared with previous studies (see Ramli et al, 2008 ; Yusoff, 2010 ; Yusoff et al, 2011 ). These findings suggest that low socioeconomic status (see also Ong, Chandran, Lim, Chen, & Poh, 2010 ), high academic pressure and the lack of parental support are significantly linked to the risk factors that may lead to academic failure or poor performance as well as disciplinary problems at school.…”
Section: Are Malaysian Adolescent Students At Risk?mentioning
confidence: 58%
“…A study on depressive symptoms and perceived competence in secondary school students in China reported that depressive symptoms was highest in students who perceived themselves to be relatively incompetent academically . Academic‐related stressor was reported to have the strongest association with stress, anxiety and depressive symptoms in secondary school students in Kuala Lumpur, Malaysia . The association between academic performance and depressive symptoms was not directly investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%